Random-term-absent addition-min fuzzy relation inequalities and their lexicographic minimum solutions - Yang, Xiao-Peng (Fuzzy sets and systems, 2022)
Addition-min fuzzy relation inequalities are a recently proposed model for describing the transmission mechanism in a peer-to-peer (P2P) network system. Considering the random line faults that take place between two terminals in a P2P network system, we propose a new kind of model, namely, random-term-absent (RTA) addition-min fuzzy relation inequalities. Some of their relevant properties are investigated in this paper. In addition, to decrease the network congestion under a fixed priority grade of the terminals, we introduce the lexicographic minimum solutions of RTA addition-min fuzzy relation inequalities. An efficient algorithm is developed to find the unique lexicographic minimum solution with an illustrative example.